2014
DOI: 10.1371/journal.pone.0100435
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Preferences for Participation in Treatment Decision-Making at the End of Life: Qualitative Interviews with Advanced Cancer Patients

Abstract: PurposePatients are often encouraged to participate in treatment decision-making. Most studies on this subject focus on choosing between different curative treatment types. In the last phase of life treatment decisions differ as they often put more emphasis on weighing quantity against quality of life, such as whether or not to start treatment aimed at life prolongation but with the possibility of side effects. This study aimed to obtain insight into cancer patients' preferences and the reasons for patients' p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 51 publications
(51 reference statements)
1
94
0
8
Order By: Relevance
“…With progression of the disease and transition to a focus on palliative care, oncologists should elicit once more what decisional model patient prefers and tailor their communication style accordingly [16] .…”
Section: Conclusion and Implications For Clinical Practicementioning
confidence: 99%
See 3 more Smart Citations
“…With progression of the disease and transition to a focus on palliative care, oncologists should elicit once more what decisional model patient prefers and tailor their communication style accordingly [16] .…”
Section: Conclusion and Implications For Clinical Practicementioning
confidence: 99%
“…It has also been demonstrated that patients' preferences can change with disease progression towards a more active participation in the later phases [16,17] . A qualitative interview study with 28 advanced cancer patients showed that, in palliative care, patients prefer their oncologists to have a shared role in decision-making.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For future research, we therefore recommend a quantitative and longitudinal study to show how patients' preferences regarding participation in rheumatology/chronic care may change over time. Changing preferences with regard to patient participation have been studied previously in end-of-life decisions (198,199), but according to our knowledge this has not been studied in chronic care where patients establish a long term relationship with their health care professionals.…”
Section: Future Sdm Researchmentioning
confidence: 99%